1991
DOI: 10.1002/app.1991.070430406
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane membranes from polyether and polyester diols for gas fractionation

Abstract: SYNOPSISPolyurethane prepolymers were prepared in ethylacetate from TDI and poly(oxypr0-pi1ene)glicols) (PE-PU) or poly(tetramethyleneglyco1adipate)diols (PES-PU) of different molecular weights (M). Homogeneous membranes were prepared by spreading the prepolymer solution added with a three, four or pentafunctional crosslinking agent, in the presence of stannous octoate as a catalyst. On increasing M, the PUS Tg decreases regularly in the range +30 to -47°C. PU's are amorphous with the exception of PES-PU obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Examination of the data for the PO-and BO-based diols (Tables 2a and 2b) further indicates that an increase in diol molecular weight results in increased permeability. These observations correlate with what has been observed in other polyurethane-based systems [23][24][25].…”
Section: Model Compound Components For Polymer Filmssupporting
confidence: 91%
See 1 more Smart Citation
“…Examination of the data for the PO-and BO-based diols (Tables 2a and 2b) further indicates that an increase in diol molecular weight results in increased permeability. These observations correlate with what has been observed in other polyurethane-based systems [23][24][25].…”
Section: Model Compound Components For Polymer Filmssupporting
confidence: 91%
“…The high gas permeability observed for the thermoplastic polymer containing B500 is most probably related to the poor quality of the polymer (low T, thermoplastic), rendering an accurate permeability determination difficult. The lack of a correlation between permeability and polymer functionality agrees well with a study which shows that permeability and diffusivity are not strongly dependent upon functionality in a polyurethane system [25]. However, further studies involving the systematic vari- The mechanism of gas diffusion is believed to be different above and below the glass transition temperature of a polymer [26].…”
Section: Effect Of Isocyanate Functionality On Permeabilitysupporting
confidence: 67%
“…Apart from PDMS, polyurethanes are types of polymers with rubbery behavior that have been used for gas separation and improvement of gas permeation in MMMs [26][27][28][29][30][31][32][33]. Polyurethanes consist of two segments: a soft segment which contains a polyester or polyether and a hard segment which is formed by extending a terminal diisocyanate with a low molecular weight diol [34].…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers [11][12][13][14][15][16][17] have shown that the gas permeability of polyurethane membranes increases with the decrease of the hard segment content and the increase of the soft segment molecular weight. In addition, a correlation has been established between the gas permeability and the chemical nature of the polyols and chain extenders.…”
Section: Introductionmentioning
confidence: 99%